2001
DOI: 10.1046/j.1365-3156.2001.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term reproductive health consequences of female genital cutting in rural Gambia: a community‐based survey

Abstract: SummaryThis paper examines the association between traditional practices of female genital cutting (FGC) and adult women's reproductive morbidity in rural Gambia. In 1999, we conducted a cross-sectional community survey of 1348 women aged 15±54 years, to estimate the prevalence of reproductive morbidity on the basis of women's reports, a gynaecological examination and laboratory analysis of specimens. Descriptive statistics and logistic regression were used to compare the prevalence of each morbidity between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
147
7
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(168 citation statements)
references
References 16 publications
11
147
7
3
Order By: Relevance
“…14,23 However, in the study conducted in rural Gambia all operations were undertaken by traditional operators also similar to the findings by SOAT et al in Sudan who found that more than 60 percent of those performing genital mutilation are traditional midwives. 24 Negative attitudes toward FC could play a significant role in the persistence of this practice in Sudan, in this study the attitude towards female circumcision was generally Negative attitude, i.e. encouraging it.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…14,23 However, in the study conducted in rural Gambia all operations were undertaken by traditional operators also similar to the findings by SOAT et al in Sudan who found that more than 60 percent of those performing genital mutilation are traditional midwives. 24 Negative attitudes toward FC could play a significant role in the persistence of this practice in Sudan, in this study the attitude towards female circumcision was generally Negative attitude, i.e. encouraging it.…”
Section: Discussionmentioning
confidence: 51%
“…This finding Similar to results of the study conducted in Gambia found that most women think that female circumcision could be eradicated by health education. 16 While contrasting with Ibekwe et al, who in 2012, found that the some respondents suggested capital punishment and Government intervention as best ways of curbing the practice. 11 The prevalence of FC in this study was (80.2%) which is slightly higher than the prevalence of a study done in Ethiopian by Daniel et al, who in 2014 found that FC prevalence 78.5%.…”
Section: Discussionmentioning
confidence: 89%
“…The practice is coded into four types 3 , the most common type (II) account for up to 80% of all cases, while the most extreme type (III) constitutes about 15% of the total procedures. The health consequences vary according to the type and severity of the procedure performed 4 . Immediate complications include severe pain, shock, hemorrhage, urine retention, and injury to adjacent tissue or death.…”
Section: Introductionmentioning
confidence: 99%
“…Obermeyer reviewed the literature on the health consequences of FGC (8). Analysis of studies on infertility or urinary problems of FGC did not document significant differences between women who had undergone FGC and those who had not (9). Studies of delivery problems showed only significantly increased rates of cesarean section and episiotomy among circumcised women.…”
Section: Health Problems In Relation To Fgcmentioning
confidence: 99%